REPRESENTASI BUDAYA ETNIS PADA PROGRAM TELEVISI ETHNIC RUNAWAY EPISODE SUKU SAMBORI - Aditya Dimas Pratama (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
This research presents an ethnic culture in the meaning of denotation, connotation, and myths that appear in episodes of Ethnic Run Away of the Sambori Tribe that broadcasted on Trans TV. The data in this research obtained from Ethnic Run Away television program episode Tribe Sambori which served on Trans TV channel. In discussing on this research, intercultural communication concepts being used and Adorno’s thought about non identity in negative dialectics. The result showed that there are five scenes in the impression particulary representative Tribe Sambori. And then from that scenes could be identified that myth about Tribe Sambori such as Sambori is communities from Tribe Bima which live in Sambori village, Bima district, Nusa Tenggara Barat province. Sambori also have the uniqueness of its own, both from history’s side and culture. By analyze the sign in the form of audio-visual aspects, this research conclude that the impressions of Ethnic Run Away Episode Tribe Sambori can’t be separated from a dominant edilogy likes etnocentrism.